Edukasi Bijak Dalam Penggunaan Teknologi dan Informasi (Media Sosial) Bagi Karang Taruna Desa Embung Kandong Melalui WAG - Rahayu Susanti, Dwi; Shofwatunnida; Mutia Perwita Sari (Universitas Hamzanwadi, 2025)
The increasingly advanced digital era and the development of technology and information through WhatsApp Groups (WAG) currently provide convenience in communicating and quickly obtaining information, but at the same time also quickly in the misuse of information dissemination. Therefore, this wise educational activity in the use of technology and information through WhatsApp Groups (WAG) aims to increase digital literacy and awareness of healthy social media for members of the Embung Kandong Village Youth Organization. The methods used include delivering materials, interactive discussions, and providing case examples related to digital ethics, data security, and preventing the spread of false information. The results of the activity show that members of the Youth Organization have increased their understanding of the responsible use of social media, including the ability to sort information, maintain privacy, and communicate ethically in the digital space. Education through WAG has proven effective as a flexible, easily accessible learning tool and is able to encourage active participation of participants. Thus, this activity contributes to forming wiser and more productive digital behavior among village youth so that they are wiser in using social media.